2010
DOI: 10.1111/j.1468-3148.2009.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomized‐Controlled Trial of Interventions to Improve Health for Adults with Intellectual Disability Who Live in Private Dwellings

Abstract: Background  People with intellectual disability who live in the community often have poor health and healthcare, partly as a consequence of poor communication, recall difficulties and incomplete patient health information. Materials and Methods  A cluster randomized‐controlled trial with 2 × 2 factorial design was conducted with adults with intellectual disability to investigate two interventions to enhance interactions among adults with intellectual disability, their care providers and general practitioners (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(151 citation statements)
references
References 20 publications
4
146
1
Order By: Relevance
“…To be included, the study population had to be adults with intellectual disability, include a prospective intervention with a comparison group, and have allocation occurring at GP level or higher, to guard against carry-over effects within general practice. Two randomised trials were found, 6,7 and one cohort study. 5 One study investigating the effect of repeated screens was excluded due to allocation occurring within general practice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To be included, the study population had to be adults with intellectual disability, include a prospective intervention with a comparison group, and have allocation occurring at GP level or higher, to guard against carry-over effects within general practice. Two randomised trials were found, 6,7 and one cohort study. 5 One study investigating the effect of repeated screens was excluded due to allocation occurring within general practice.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Barriers to providing satisfactory health care include difficulties gaining access, short consultation times, and communication difficulties. 4 Beneficial effects of health screening in adults with intellectual disability have been reported; [5][6][7] however, recruitment in this population is difficult, 4,8 and individual studies have been small and effect estimates unstable. This study has addressed this by conducting a pooled analysis to assess the overall benefits of health screening for adults with intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…20,22 These noted a non-significant trend towards new disease detection after 1 year, but they did not report the extent to which needs had been met or obtain data about health monitoring needs. Unlike our trial, they showed an increase in health-promotion activity, especially with testing of vision and hearing, giving tetanus boosters, and checking hepatitis B serology; in our trial the nurses enquired about vision difficulties and testing, then directed people towards an optometrist, rather than directly testing vision, and the health check did not include hepatitis B serology, so data are not similar.…”
Section: Discussionmentioning
confidence: 99%
“…21 Results from another Australian cluster trial that randomly assigned 272 participants to combined health advocacy with the GP-delivered health assessment, or standard care, showed no additional benefits for the intervention. 22 The extent of health actions from these checks was greater than that recorded in GP records. 23 However, the health-care system in Australia differs from the that in the UK (eg, patients do not register with a GP), and many organisations provide paid support, so results might not be generalisable.…”
Section: Introductionmentioning
confidence: 91%
“…5,6 Applying health assessments by means of questionnaires, focusing on highly prevalent diseases for people with ID, have proven to be an effective method to detect health needs, and can play an important role in health monitoring and health promotion. [7][8][9][10][11] Research has shown increased disease detection, as well as an increase in prevention and health promotion activities. [7][8][9][10] Most patients with ID valued the use of health assessment instruments positively.…”
Section: Introductionmentioning
confidence: 99%